Simulation of the process of formation of layered condensates at EB-PVD of binary systems of Cu−Cr type - Kurochkin, V.D. (Reports of the National Academy of Sciences of Ukraine, 2014)
The mechanism of spontaneous formation of layered condensates at the electron-beam physical vapor deposition from separate crucibles of binary metallic systems is discussed. Simulation of crystallite growth by the kinetic Monte Carlo method shows that the competitive mechanism leads to a nonlinear dependence of the crystallite growth rate in each phase on the density phase flows. The calculation of the mass transfer indicates that, as a result of the reflection from the condensate surface, atoms of the refractory component may form a shielding film of the more refractory component on the surface of a melt pool. This results in the formation of a feedback between the evaporation rate and the composition of the condensate. It is shown that, under certain conditions, this leads to the onset of self-oscillations of evaporation rates and establishing the oscillatory, aperiodic, or stochastic condensation modes. With fluctuations of the temperature of pools, this effect can lead to the formation of layered structures with complex hierarchies of the thicknesses of layers that are observed in real condensates.